EDUKASI BAHAYA KOSMETIK PALSU UNTUK MENINGKATKAN PENGETAHUAN SISWA SMK NEGERI 6 KENDARI - Muhammad Ilyas Y.; Lidya Agriningsih Haruna; Asriullah Jabbar; Nasrudin Nasrudin; Halik Halik; Sri Rasniawaty; Hajir Mayana; Aulia Amala; Nur Mardatillah Al Mubaidillah; Yulidyah Syaffanie Lilikay; Mubarak Mubarak; Adriatman Rasak; Apriyanto Apriyanto; Nurhikma Nurhikma (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Adolescence is a vulnerable phase for exposure to counterfeit cosmetics, especially with the widespread influence of social media. Low student awareness about safe and legal cosmetics is a primary issue that needs to be addressed. This community service activity aimed to increase the knowledge and awareness of students at SMK Negeri 6 Kendari regarding the dangers of counterfeit cosmetics and how to verify products through the National Agency of Drug and Food Control (BPOM). Methods included pre-test, interactive lecture counseling, educational brochure distribution, BPOM product checking practice, and post-test. The activity was conducted in June 2026 at SMKN 6 Kendari. Results showed a significant improvement in students' understanding, indicated by increased post-test scores compared to pre-test. Students were able to identify characteristics of counterfeit cosmetics, recognize hazardous substances such as mercury and hydroquinone, and independently verify product legality through the BPOM website. This activity is expected to make students smart consumers who prioritize safety and health in choosing cosmetic products